Hostile intent [large type] - Eason, Lynette (Eason, Lynette. Danger never sleeps., 2021)
"FBI Special Agent Caden Denning is part of the task force assigned to catch a serial killer targeting military families-only he needs Ava Jackson's help to do so. When the killer turns his sights on Ava, the investigation turns into a fight to survive"--"--